Evaluation of patties prepared from combination of beef and antelope meat (2016)
This study was carried out in the Meat Science laboratory of the Department of Animal Production, Olabisi Onabanjo University, Yewa Campus, Ayetoro, Ogun State to evaluate patties prepared from beef and antelope meat. Fresh beef and antelope meat of 3kg each were purchased, chilled and allowed to equilibrate to room temperature 27˚C which were ground. Approximately 2.3 kg of each meat type was apportioned into five parts of 0, 25, 50, 75 and 100 % after mixing the two meat types into 0, 115, 230,345 and 460g of antelope meat. The meat patties samples were cooked using broiling method and cooled at room temperature. Physico- chemical characteristics and organoleptic attributes of the meat product Were determined after cooking. The results revealed that the cooking loss (32.43%) was higher (p< 0,05) at T4 followed by T5 (31.48%) while the patties yield (71.97%) was in TO followed by patties in T2 (70.45%) and T3 (70.35%) respectively. Water holding capacity (WHC) was higher in T2 and T3 (67.00%) and (66.20%) followed by TO with 62.00%, hence lower shear force values of 0.58N, 0.62N and 0.70N. Moisture content (50.90%) was higher (p< 0.05) T1 and T2 (59.15%), protein was higher (p< 0.05) in 75, while fat was least (p<0.05) in T4 (8.25 %) and T5 (8.20%) in cooked patties. Patties in Tl, T2 and T3 with 6.50, 6.80 and 6.62 were accepted mostly as the had higher colour values of 7.25, 6.03 and 6.21. It was observed that inclusion of antelope meat in the patties between 25% and 50% sufficed to provide the nutrients and flavour that consumers needed in meat patties prepared from beef and antelope meat combination in this study. Therefore, antelope meat could be included in meat patties not beyond 50% so that consumers could relish the meat product.